International Law English for Spesific Purpose of State Management Overview Preparatory Subject Design as Basic Material - Pamuji, Wirawan; Maslon Hutabalian; Achmad Feryliyan (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
International English Law state management Progress requires preparation material to comply further material afterwards, it conducts followed selection subject learnt before students take a part of the next class in International term. The Research applies Research and Development Method in designing Developing Method of Inquiry Strategy in applied design of material English Law Material. The Design is applied using design as the strategy implies to the real field of practical implementation of International class application of Law in State Management overview